Microsatellite instability among individuals of Hispanic origin with colorectal cancer - Gupta, Samir (2010)
BACKGROUND: Though the presence of microsatellite instability (MSI) in patients with colorectal cancer (CRC) may have implications for prognosis, therapy, and family counseling, MSI prevalence is not well described among individuals of Hispanic origin in the United States (US) with CRC. METHODS: We conducted a retrospective cohort study employing a hospital-based tumor registry to identify individuals of Hispanic origin diagnosed with CRC. Clinical data and tumor samples were retrieved. Molecular analyses included testing for MSI using a panel of 5 mononucleotide markers (BAT25, BAT26, NR21, NR24 and NR27) in a pentaplex polymerase chain reaction assay, as well as immunohistochemistry for the MMR proteins MLH1, MSH2, MSH6, and PMHS2 on representative tissue. RESULTS: 111 individuals of Hispanic origin with CRC were identified. 41.1% were women, median age was 57 years (IQR:47.1–63.5). 11 (9.8%, 95%CI:4.2–15.6) had MSI CRC, while 14 (14.6%, 95%CI:7.3–21.8) had CRC with≥1 MMR protein abnormality. 10 of 11 individuals with MSI had clinical or molecular characteristics suspicious for Lynch syndrome such as abnormal expression of MSH2 and/or MSH6 (n=7) or age<50 at diagnosis (n=7). CONCLUSIONS: The prevalence of MSI CRC among Hispanic individuals may be similar to other races and ethnicities, but clinical-pathological characteristics, including age at diagnosis and pattern of abnormal MMR protein expression, suggests that sporadic MSI CRC may be less common in individuals of Hispanic origin, and that much MSI observed in this situation may be attributable to Lynch syndrome. Further exploration of the causes of disparate presentations of CRC by ethnicity and race is warranted.